Development of Learning Media for Sprechen A2 Course Based on Traditional Games of North Sumatra - Hutagalung, Surya Masniari; Huszka, Balazs; Sari, Tanti Kurnia (Jurnal Ilmu Pendidikan, 2023)
The development of learning media in this research is part of the development of Sprechen A2 learning tools based on the case method and team-based project. The development model used is the Richey and Klein (2007) development model with planning, development, and evaluation stages. This research produced five sets of vocabulary cards played in groups. This game trains vocabulary mastery according to the A2 theme and sentence formation. The development results were reviewed by experts and given input. The results of the expert review stated that the developed game cards are suitable for use with a score of 92 or with a category of excellent. This result indicates that the word game cards are suitable for use. Expert input regarding adding vocabulary sets will be carried out as further development. The game cards are then played alternately in the Sprechen A2 learning class according to the discussion theme. At the end of the learning process, a questionnaire was distributed to students to determine their response to the use of game cards. The questionnaire contains five questions, all answered with 100% agreement. This means that the student response is positive and worthy of further development